Development of a Four Tier Diagnostic Test Instrument Based on iSpring Suite 9 to Identify Understanding of Concepts in Students: Pengembangan Instrumen Four Tier Diagnostic Test Berbasis iSpring Suite 9 Untuk Mengidentifikasi Pemahaman Konsep Pada Mahasiswa - Asri Nurhafsari; Febri Rismaningsih (Borneo Educational Journal (Borju), 2023)
Evaluation is important to measure the achievement of learning outcomes. Multiple choices, form of test, is commonly used in learning evaluation. However, in the real situation shows that multiple choice tests make students choose the answers randomly. This study was conducted to provide a solution by developing a Four Tier Diagnostic Test based on iSpring Suite 9 to identify students' conceptual understanding of Static Fluid. This research methodology employed Research & Development (R&D). The subject in this study were students of the Faculty of Engineering at Universitas Islam Syekh-Yusuf who are studying Basic Physics. Data collection techniques use observation, interviews, tests, validation sheets, and questionnaires. The validation results of material experts are 93%, media experts are 84% so that they are included in the very feasible category. The validity of the test showed that 35 items were valid, and 7 questions were invalid. The reliability of the test is 0.93. The index of difficulty consists of 3 easy, 35 moderate and 4 difficult. The discriminating power of each item included 16 very good questions, 9 good questions, 11 enough questions, 5 bad questions and 1 very bad item. Student response to this instrument is 74.83% included in the high category. This test can identify four levels of students' understanding of concepts, namely understanding concepts, not understanding concepts, partially understanding and misconceptions. Based on the results, the Four Tier Diagnostic Test based on iSpring Suite 9 has met the criteria for a good instrument and is suitable for use.